2018
DOI: 10.1371/journal.pone.0191340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of earthquake on perinatal outcomes: A Chilean register-based study

Abstract: BackgroundNatural disasters increase the level population stress, including pregnant women, who can experience prenatal maternal stress, affecting the fetus and triggering perinatal complications, such as low birth weight, smaller head circumference, etc. However, little is known about effects of earthquake on perinatal outcomes.ObjectiveTo evaluate the effect of earthquake occurred on February 27, 2010 and perinatal outcomes of Chilean pregnant women, and to examine these effects by timing of exposure during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…The ZHB was performed in the aftermath of Hurricanes Irma and Maria, which had a significant impact on the USVI and may have limited attendance at the ZHB due to logistical difficulties (e.g., inability to contact, transportation, no longer living in the USVI) or socioeconomic strain. Moreover, natural disasters have been associated with reduced fetal growth, mental health issues in the post-natal period in both mothers and children, increased likelihood of acute illness, and decreased height and weight development in children [ 25 , 26 , 27 , 28 ]. The effect these natural disasters may have had on the development of these children and how they may have independently influenced the findings of this report is unknown [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ZHB was performed in the aftermath of Hurricanes Irma and Maria, which had a significant impact on the USVI and may have limited attendance at the ZHB due to logistical difficulties (e.g., inability to contact, transportation, no longer living in the USVI) or socioeconomic strain. Moreover, natural disasters have been associated with reduced fetal growth, mental health issues in the post-natal period in both mothers and children, increased likelihood of acute illness, and decreased height and weight development in children [ 25 , 26 , 27 , 28 ]. The effect these natural disasters may have had on the development of these children and how they may have independently influenced the findings of this report is unknown [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present findings imply that the type of stress and the stage when a pregnant woman is exposed to stress might affect her and her fetus differently. Palmeiro‐Silva et al . found that male newborns who were exposed to stress during the second trimer had a shorter gestation, whereas female newborns showed no such association, suggesting that the risk of a shorter pregnancy varies by fetal gender.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on disaster-related short-term adverse birth outcomes have produced mixed results between different earthquakes, with some studies, including one in Sichuan, China, showing increased risks of LBW, PTB, and SGA [ 7 , 8 , 24 ], while others studies suggesting nonsignificant changes in adverse birth outcomes [ 25 , 26 ]. Furthermore, the findings on the same disasters, Hurricane Katrina for instance, have also been inconsistent [ 27 , 28 ], indicating further research is likely needed to understand the effects on birth outcomes.…”
Section: Discussionmentioning
confidence: 99%